Bacterial topoisomerase I as a target for discovery of antibacterial compounds - Yuk-Ching Tse-Dinh (2008)
Bacterial topoisomerase I is a potential target for discovery of new antibacterial compounds. Mutant topoisomerases identified by SOS induction screening demonstrated that accumulation of the DNA cleavage complex formed by type IA topoisomerases is bactericidal. Characterization of these mutants of Yersinia pestis and Escherichia coli topoisomerase I showed that DNA religation can be inhibited while maintaining DNA cleavage activity by decreasing the binding affinity of Mg(II) ions. This can be accomplished either by mutation of the TOPRIM motif involved directly in Mg(II) binding or by altering the charge distribution of the active site region. Besides being used to elucidate the key elements for the control of the cleavage-religation equilibrium, the SOS-inducing mutants of Y. pestis and E. coli topoisomerase I have also been utilized as models to study the cellular response following the accumulation of bacterial topoisomerase I cleavage complex. Bacterial topoisomerase I is required for preventing hypernegative supercoiling of DNA during transcription. It plays an important role in transcription of stress genes during bacterial stress response. Topoisomerase I targeting poisons may be particularly effective when the bacterial pathogen is responding to host defense, or in the presence of other antibiotics that induce the bacterial stress response.